(untitled) (diségno, 2023)
The book, published in 2002 by the Massachusetts Institute of Technology under the title Origins, Imitations, Conventions: Representation in the Visual Arts (fig. 1), is a collection of 12 essays written by Ackerman since 1994. James S. Ackerman (1919-2017) has been one of the leading scholars of Renaissance architecture in the last century. Disciple of Henri Focillon and fellow student of Richard Krautheimer and Erwin Panofsky, he was a professor at Cambridge and Harvard Universities in the United States. On the occasion of his death, Carlo Olmo wrote of his work: “His history of architecture is in touch with other historiographies, turning even over-studied architectures into examples that help the reader to understand how many keys are needed to prevent reducing the narration of architecture, which Ackerman treats with true passion, to a mere description or a genealogical history.” His works include The Architecture of Michelangelo from 1961 (Italian ed. Einaudi 1968), Palladio from 1966 (Italian ed. Einaudi 1972) and La Villa from 1990 (Italian ed. Einaudi 2013). [read more]